Control de Ingresos y Gastos de la Empresa Altec S.A. de la ciudad de Babahoyo - Barahona Olaya, Jennifer Estefania (2019)
In the present work the case study is carried out with subject "CONTROL OF INCOME AND EXPENSES OF THE COMPANY ALTEC SA IN THE CITY OF BABAHOYO", where it will be announced the control of income and expenses of ALTEC SA is a company forced to carry accounting that offers services of manufacture and installation of windows, doors, everything related to aluminum, glass and wood, of the best quality with a local and national market. It is constituted as a limited company, being a commercial company the inventory is the one that involves the acquisition costs. It is important that companies keep track of what comes in and what goes out, by the activities they do, involving cash transactions, checks, invoices and other receipts. Through the technique of interviewing the accounting department, control tests will be carried out on the income and expense accounts, the comparison and analysis of the comprehensive income statement, the sales sales process and production sales. The case study is oriented in the sub-line of investigation of Accounting Information Management, the objective of this work is to show how the control of income and expenses is determined; basic conceptualizations that help the interpretation of the subject and its problems will be presented, with bibliographies and investigations that make known the importance of an efficient and effective control of income and expense accounts.